ChemInform Abstract: Alkene Carboboration Enabled by Synergistic Catalysis. Issue 11 (March 2015) - Smith, Kevin B.; Logan, Kaitlyn M.; You, Wei; Brown, M. Kevin
Abstract A synergistic Cu/Pd catalytic system allows the regioselective cross‐coupling of in situ generated secondary Csp3—Cu nucleophiles.